2007
DOI: 10.1007/s00383-006-1857-7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of IL8 gene polymorphisms with familial vesico-ureteral reflux

Abstract: Vesico-ureteral reflux (VUR) is the most common inherited disorder of the lower urinary tract. Children with VUR are at risk for ongoing renal damage with subsequent infections. IL8 is an important inflammatory mediator which can be produced by epithelial cells of the renal tract in response to a variety of inflammatory stimuli. High serum concentrations of IL-8 have been reported in patients with chronic renal failure. Elevated IL-8 levels have been reported in the urine of patients with VUR and renal parench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…It can then participate in the progress of anti-infection and inflammatory disease. With regards directly to OCD, recent studies indicated that cytoactive material such as inflammatory factors may participate in the aetiology of OCD (24). In addition, it is of interest that serum levels of IL-12 were found to be increased in a group of 14 patients with acute Sydenham's chorea compared with control serum (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can then participate in the progress of anti-infection and inflammatory disease. With regards directly to OCD, recent studies indicated that cytoactive material such as inflammatory factors may participate in the aetiology of OCD (24). In addition, it is of interest that serum levels of IL-12 were found to be increased in a group of 14 patients with acute Sydenham's chorea compared with control serum (8).…”
Section: Discussionmentioning
confidence: 99%
“…Its association with other mental disorders such as TS was also been reported (7). With regards directly to OCD, recent studies indicated that cytoactive material such as inflammatory factors may participate in the aetiology of OCD (24). Given that IL-12 is the strongest cytoactive material stimulating cellular immunity to date, IL-12 is worth to be investigated as a candidate gene, which might be related to OCD.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, four studies did not describe the ethnicity of the participating population of the study [38,41,48,54]. Five studies were prospective [32,38,42,44,50], and the other studies did not specify the design, but based on their description in the "method" section, these latter studies can be considered to be retrospective.…”
Section: Quality Of the Studiesmentioning
confidence: 97%
“…Based on the criteria for assessing the quality of the studies (Table 1), 11 studies (61%) were identified as being of a poor quality design [32,38,41,44,45,[47][48][49][52][53][54].…”
Section: Quality Of the Studiesmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood leukocytes using standard methods. The polymorphisms at -511 C/T in the promoter region of IL-1b were genotyped by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) according to the procedure described by Kuroda et al [22]. For all data of patients and controls, the Hardy-Weinberg equilibrium of the genotype distribution was tested using the homogeneity chi-square test.…”
Section: Dna Analysis and Statistical Analysismentioning
confidence: 99%